Психологические особенности больных с головной болью напряжения обусловленые остеохондрозом шейного отдела позвоночника - Насибуллин, Б.А.; Соловьев, Ю.Ю.; Гоженко, Е.А. (Медична гідрологія та реабілітація, 2010)
Проведений аналіз психологічних особливостей головного болю напруги на тлі остеохондрозу шийного відділу хребта. За даними комплексного обстеження даної категорії хворих, виявлені особливості психологічного статусу поєднаного перебігу вищезгаданих захворювань, які виражаються в істотному зниженні якості життя даної категорії хворих. The analysis of psychological features of head pain of tension on a background the osteochondrosis of neck department of spine is conducted. From data of complex inspection of this category of patients, the features of psychological status of sochetannogo flow of foregoing diseases which are expressed in the substantial decline of quality of life of this category of patients are exposed.